Pola Asuh Orang Tua terhadap Sosioemosional Anak Tunarungu Usia Sekolah - Farial Nurhayati; Ningning Sri Ningsih (Jurnal Kesehatan, 2017)
WHO said the number of children with special needs in Indonesia was around 7% of the total number of children aged 0-18 years, or amounting to 6.23 million, in 2007. The delay in the development of language skills were resulted in low academic achievement. Parenting is interaction between children and parents in terms of educating, guiding, and discipline, also protecting the child to reach maturity in accordance with the norms that exist in society. This study was to determine the relationship between parenting style with deaf children’s socioemotional. It was cross sectional research methods with 42 respondents. Respondents were parents of deaf children at extraordinary school in the city of Bogor. Statistical test results were obtained by p-value=0.183, it can be concluded there was no significant association between parenting style with socioemotional deaf children. Arman et all (2008) said socioemotional factors that affected a child were the following individual risk factors, such as child temperament, age, gender, developmental delays, serious health problems, family factors and environmental factors.